Evolution of quantum correlations of two qubits in a cavity with biphotonic dissipation - Molinares Garrido, Hugo Andrés; Villamil Barrios, Pablo Emilio; Eremeev, Vitalie (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In this work we study the evolution of quantum correlations in a Tavis-Cummings model that consists of two qubits and a single quantized mode of the electromagnetic field. The processes of emission / absorption of a single photon and of two correlated photons are considered for each of the qubits. The model is studied taking into account unifotonic and biphotonic dissipations, through a cavity that interacts with a thermal reservoir. The numerical solution of a Lindblad master equation allows us to make a description of the evolution of quantum correlations, quantum entanglement and quantum discord, as a function of time for an atomic state type superposition. It is shown that the different results of the quantum correlations present qualitatively different behaviors in their evolution.